Determination of Job Satisfaction and Company Performance: Analysis of Competence, Self-Efficacy and Work Motivation - Peppy Fachrial; R. Rina Novianty Ariawaty (Dinasti International Journal of Education Management And Social Science, 2024)
The purpose and benefits of this literature review research are expected to build hypotheses regarding the influence between variables, which can later be used for further research in the scope of human resource management. The literature review research article on the determination of job satisfaction and company performance: Analysis of Competence, Self-Efficacy and Work Motivation is a scientific article in human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique uses literature studies or a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Competence influences Job Satisfaction; 2) Self-Efficacy influences Job Satisfaction; 3) Work Motivation influences Job Satisfaction; 4) Competence affects Company Performance; 5) Self-Efficacy affects Company Performance; and 6) Work Motivation affects Company Performance.